Spatial and temporal structure of Cerrado Conservation Units: combined heterogeneity for conservation - Santos, Sara Alves; Cherem, Luis Felipe Soares (Sociedade & Natureza, 2022)
Unidades de Conservação - UC (type of Brazilian protected area) corresponds to approximately 18% of the national continental area, resulting from the integration of pressures from organized civil society materialized in public policies, whose selection criteria and distribution have varied over time. By observing the location of these protected areas, issues related to their relevance and Cerrado heterogeneity representativeness are of considerable importance for the conservation of life, since they make it possible to understand this Biome’s current situation, perspectives, and challenges for its conservation. Therefore, the objective here is to evaluate the spatial distribution of UC in the Cerrado from the temporal evolution of new units’ creation, in administrative spheres and categories, with a period starting in 1949, the year of the first UC creation in the Cerrado, until the end of 2010. The methodological procedures adopted consisted of a bibliographic survey, secondary databases consultation and data processing in a GIS environment. The results show that the distribution of UC is not regular in either space or time. In addition, many units correspond to isolated fragments of vegetation, with no connection to other areas and/or are of smaller dimensions, making it difficult to maintain the ecosystems present in them. In the national scenario, the Cerrado stands out in relation to the number and area of protected ones, which reinforces its important role in Brazilian conservation policies.